Pengaruh Job Insecurity dan Kemampuan Kerja terhadap Kepuasan Kerja pada PT FWD Insurance Kawasan Megamas Manado - Rewur, Gabriela Serafina (JURNAL ADMINISTRASI BISNIS, 2026)
This study aims to analyze the influence of job insecurity and work ability on job satisfaction at PT FWD Insurance Megamas Area, specifically among agents/employees. Data were collected through questionnaires distributed to 68 selected respondents using purposive sampling. The data were analyzed using multiple linear regression. Partial Test (t-test) Results: Job insecurity did not show a significant effect on job satisfaction (significance value > 0.05). Work ability had a significant effect on job satisfaction (significance value < 0.05), meaning that improvements in work ability lead to increased job satisfaction. Simultaneous Test (F-test )Results: Both variables together had a significant effect on job satisfaction, as evidenced by a significant F value (p < 0.05). Coefficient of Determination (R²): The R² value of 0.561 (or 56.1%) indicates that job insecurity and work ability together explain more than half of the variance in job satisfaction. The remaining 43.9% is influenced by other factors not included in this study. Conclusion: Job insecurity does not significantly affect job satisfaction when viewed individually, while work ability has a significant positive effect. However, when both variables are considered simultaneously, they significantly influence job satisfaction, albeit with differing contributions.